Osteotomy training for dental students using three‐dimensional simulation software and maxillofacial three‐dimensional‐printed models. Issue 5 (3rd January 2022) - Yoshida, Shuji; Watanabe, Akira; Sugahara, Keisuke; Odaka, Kento; Katakura, Akira; Takano, Masayuki
Abstract: Purpose/objectives: Simulated educational models of teeth, bones, and gums have been used for a long time in procedural skills training in dentistry.  The advent of three‐dimensional (3D) printing technologies and additive manufacturing has facilitated the production of more advanced 3D printed models that can be utilized for surgical and dental training together with other technologies (e.g., 3D scanners and image analysis software). Methods: We conducted training on osteotomy in the maxilla and mandible using maxillofacial simulation software (MSS) and a 3D‐printed model for 5th‐year undergraduate dental students (13 students in 2017 and 11 students in 2018 with more than half of their results). We compared the group (13 students) who performed osteotomy after participating in the simulation lecture with those (11 students) who performed osteotomy after performing self‐simulation (they were instructed to bring their personal computers and install the MSS) using tests and questionnaires (pre‐ and post‐curriculum). Results: The average test score was significantly higher in the group who performed osteotomy using the 3D‐printed model after performing self‐simulation; participants in this group had acquired a better understanding of the surgical procedure. Comparison using questionnaires showed a significant difference in the students' understanding of instruments and surgical techniques between both groups. Conclusion: The MSS and 3D printed models are widely used clinically. Incorporating these in the curriculum will help accelerate student development. In addition, prompt education on the purpose and usefulness of these tools will not only facilitate simulation software and 3D‐printed model‐based treatment plan in the clinic but also promote further research.